Macrophytes as a substrate for the mollusc Dreissena polymorpha Pallas, 1771 development in Narochanskie lakes - Kruk, Daria V.; Zhukava, Hanna A.; Novikov, Alexey A.; Posled, Olga S.; Xiufeng, Zhang; Adamovich, Boris V. (Experimental Biology and Biotechnology, 2023)
The bivalve of zebra mussel Dreissena polymorpha has been formed a large population since the invasion into Narochanskie lakes (Naroch Lake, Myastro Lake and Batorino Lake), which is actively involved in the structural, functional and ecological processes of the ecosystem. Plenty of studies on the mussel population development in Naroch Lake and its interactions with other components of the ecosystem have been carried out since the beginning of the invasion. In addition, plenty of research has also been conducted on submerged macrophytes in the Naroch, Myastro and Batorino lakes. The results showed that the main substrate for zebra mussel development in Naroch Lake’s ecosystem are emergent plants, especially Characeae, which develop in large quantities in middle depths. In Myastro Lake, Dreissena inhabits mainly Elodea thickets due to their large abundance in the lake. Submerged macrophytes are not sufficiently dense in Batorino Lake for zebra mussel development, therefore Dreissena develops in small quantities. Thus, in the Naroch and Myastro lakes, macrophytes arranged in macrophyte zones or belts, are the main niche for the development of zebra mussel, which should be taken into account when studying the zebra mussel population.
Keywords: Dreissena polymorpha; Naroch; Myastro; Batorino; submerged macrophytes; plant substrate; spatial distribution of the population